Adaptation of Dominant Species to Drought in the Inner Mongolia Grassland – Species Level and Functional Type Level Analysis - Yan, Yongzhi; Liu, Qingfu; Zhang, Qing; Ding, Yong; Li, Yuanheng (Frontiers in Plant Science, 2019)
Plant adaptation to drought through adjusting leaf traits is one of the hot topics in plant ecology. At present, there is a deeper interpretation concerning how a single species adapts to drought by adjusting leaf traits, however, there is poor understanding of how different plant functional types adapt to drought. Therefore, in this study, 22 sample plots were arranged along the drought gradient of Inner Mongolia grassland, with the selection of 39 dominant species and the measurement of leaf functional traits in 8 plants, and adaptation strategies of plant leaves to drought were analyzed on species and functional types scales. The main results were as following: (1) Variation of plant functional traits at species level was affected by both phylogeny and climatic factors, among which specific leaf area, leaf carbon-nitrogen ratio and leaf nitrogen content were significantly affected by drought. (2) The selected 39 species were classified into 5 functional types based on plant functional traits, and there were significant differences in leaf functional traits among the 5 functional types in the 8 species. (3) The 5 plant functional types adapted to drought through 4 leaf adjustment approaches, including adjusting carbon-nitrogen ratio, specific leaf area, nitrogen content, as well as specific leaf area and nitrogen content simultaneously. (4) With the increase of drought degree, plants adapted to drought by a trade-off between increasing water use efficiency and reducing nitrogen use efficiency.